1967
DOI: 10.1038/bjc.1967.65
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic pathology in rats on low dietary levels of dimethylnitrosamine.

Abstract: DIMETHYLNITROSAMINE (DMN) is a very powerful liver carcinogen for the rat (Magee and Barnes, 1956) and will produce malignant tumours at other sites and in other species (Magee and Barnes, 1967).Because of the possible importance of certain nitrosamines as aetiological agents for cancer in the human environment (Magee and Barnes, 1967) it was important that an attempt should be made to try to obtain experimental data on the basis of which it might be possible to calculate a non-effective dose of this compound.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

1970
1970
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(20 citation statements)
references
References 6 publications
0
19
0
1
Order By: Relevance
“…Hi:LiJilffi+}:qT'$:?i::n'".[rk}ii{{"i;1,+"+{*H;'r#+};*1+:"'J"':'J'ffi';';""""? "?ii;"'""'i"'j3ffi'j';'-r"l:$l"r{ (6,18). However, from data on the acute effects of nitrosamines in short term experiments, the data obtained in this investigation indicate that there are sufficient aliphatic secondary amines present for the formation of biologically important quantities of alkyl nitrosamines either in smoke or in vivo (8,18).…”
mentioning
confidence: 61%
“…Hi:LiJilffi+}:qT'$:?i::n'".[rk}ii{{"i;1,+"+{*H;'r#+};*1+:"'J"':'J'ffi';';""""? "?ii;"'""'i"'j3ffi'j';'-r"l:$l"r{ (6,18). However, from data on the acute effects of nitrosamines in short term experiments, the data obtained in this investigation indicate that there are sufficient aliphatic secondary amines present for the formation of biologically important quantities of alkyl nitrosamines either in smoke or in vivo (8,18).…”
mentioning
confidence: 61%
“…The lowest dose given to rats was 2 ppm in their diet (Terracini et al, 1967). Concentrations used in this study ranged from 2 to 50 ppm.…”
Section: Tumorigenicitymentioning
confidence: 99%
“…In case of dimethylnitrosamine, Terracini et al [22] reported that 2 ppm in the diet caused liver tumor in 1 out of 37 rats, and 5 ppm in 5 out of 68 rats after an observation time of up to 120 weeks. Ito [personal commun.]…”
Section: Minimum Carcinogenic Dosementioning
confidence: 99%